E-Sampah Sebagai Salah Satu Wujud Smart Village; Study Analisa dan Perancangan - Assani’, Saffana; Hermanto, Hermanto (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2021)
A waste bank is a place for collecting waste which can then be exchanged for money or basic necessities. In managing transactions at the waste bank, they still use the manual method by recording every waste exchange using a ballpoint pen, the waste bank customer’s savings book, and a large notebook for the admin. The manual method causes several problems that often occur, including; lost the waste bank passbook, lost the admin notebook, needed a place to store recording tools, and miswritten or miscalculated during transactions at the waste bank. In order to overcome these problems, this study aims to make analysis and design for an application that can be used to help manage data management in waste banks. It is also the first step for a village to become a smart village. The application that will be developed is the e-samah application. This research uses an extreme programming methodology, functional and non-functional analysis, system design using UML (unified modeling language), database design using CDM (conceptual data model) and PDM (physical data model), and is planned for development using boostrap and codeigniter. . For now, the research results are in the form of analysis and design documents which can later be used as a reference in application development.